2015
DOI: 10.1111/eea.12380
|View full text |Cite
|
Sign up to set email alerts
|

Simulating effects of climate change under direct and diapause development in a butterfly

Abstract: Temperature is one of the most important ecological factors affecting species survival and distributions. Therefore, global climate change, involving increases in mean surface temperature and the occurrence of extreme weather events, may pose a substantial challenge to biodiversity. Whereas tropical ectotherms are believed to be very sensitive to climate change, temperate-zone species may actually benefit from higher temperatures. However, as in temperate zones large parts of the year are unsuitable for growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 48 publications
(109 reference statements)
1
17
0
Order By: Relevance
“…However, such detrimental effects were largely restricted to diapause survival, as we found only marginal effects during later development. The latter is in line with other studies on L. tityrus (Klockmann, Karajoli, et al, ; Klockmann, Schröder, et al, ), confirming our second hypothesis. We admit that the conditions used may not perfectly reflect natural situations, as is typically the case in laboratory studies.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, such detrimental effects were largely restricted to diapause survival, as we found only marginal effects during later development. The latter is in line with other studies on L. tityrus (Klockmann, Karajoli, et al, ; Klockmann, Schröder, et al, ), confirming our second hypothesis. We admit that the conditions used may not perfectly reflect natural situations, as is typically the case in laboratory studies.…”
Section: Discussionsupporting
confidence: 94%
“…In line with previous studies on pest species (Berzitis et al, ; Xiao et al, ), our experiments showed clearly reduced overwintering survival when diapausing larvae were exposed to warmer winter temperatures, which are expected to occur as a result of current climate change. This is a remarkable result as we tested a widespread temperate‐zone species which is considered to have a low vulnerability to climate change (Brunzel et al, ;Klockmann, Karajoli, et al, ; Klockmann, Schröder, et al, ). Such detrimental effects may be caused by higher metabolism, increasing respiration and therefore the demand for energy (Hahn & Denlinger, ; Irwin & Lee Jr, ; Stuhldreher, Hermann, & Fartmann, ; Vesterlund, Lilley, van Ooik, & Sorvari, ; Yoon & Hwang, ; but see Beekman et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we found that closely related species, arguably differing in their vulnerability to climate change, seem to differ in their responses to environmental stress. However, such variation was restricted to early developmental stages, while different levels of stress seem to have little effect on fitness during further development (i.e., in older larvae, pupae, and adults; Potter et al., ; Klockmann, Günter, et al., ; Klockmann, Karajoli, et al., ; Klockmann, Schröder, et al., ; Klockmann, Wallmeyer, et al., ). We suggest that, in the three species investigated here, stress tolerance during early development might be a major determinant of vulnerability to climate change and may explain recent population declines in L. helle along with habitat deterioration (Bauerfeind, Theisen, & Fischer, ; Fischer et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, these species may also differ in (heat) stress tolerance and concomitantly in their vulnerability to climate change, ranging from low to high risk (Ebert & Rennwald, 1991;Settele et al, 2008;Habel et al 2011; see further below and Table 1). We focus on early developmental stages because earlier studies showed that differences in vulnerability are unlikely to be caused by differential responses to thermal stress during larval and pupal development (Klockmann, Karajoli, Reimer, Kuczyk, & Fischer, 2016;Klockmann, Schröder, Karajoli, & Fischer, 2016) as well as adult stress resistance (Klockmann, Wallmeyer, & Fischer, 2017). We hypothesize that (i) mortality rates increase at higher temperature and additionally with reduced humidity in all species, (ii) and that L. helle will suffer most strongly from simulated heat and drought stress.…”
mentioning
confidence: 99%
“…Butterflies were kept for egg laying in a climate cabinet (Sanyo MLR-351H; Bad Nenndorf, Germany) under naturally fluctuating temperatures to improve ecological realism (mean 15.4°C, amplitude 5.5°C, 75% relative humidity, and L17 : D7 photoperiod; cf. Klockmann et al, 2016c). They were placed individually in translucent 1 L plastic pots and were provided with R. acetosa for egg-laying, and with fresh flowers (Crepis sp.…”
Section: Study Organisms and Egg Samplingmentioning
confidence: 99%